Forgetting emotional material in working memory. Issue 3 (20th December 2017) - Mızrak, Eda; Singmann, Henrik; Öztekin, Ilke
Abstract: Proactive interference (PI) is the tendency for information learned earlier to interfere with more recently learned information. In the present study, we induced PI by presenting items from the same category over several trials. This results in a build-up of PI and reduces the discriminability of the items in each subsequent trial. We introduced emotional (e.g. disgust) and neutral (e.g. furniture) categories and examined how increasing levels of PI affected performance for both stimulus types. Participants were scanned using functional magnetic resonance imaging (fMRI) performing a 5-item probe recognition task. We modeled responses and corresponding response times with a hierarchical diffusion model. Results showed that PI effects on latent processes (i.e. reduced drift rate) were similar for both stimulus types, but the effect of PI on drift rate was less pronounced PI for emotional compared to neutral stimuli. The decline in the drift rate was accompanied by an increase in neural activation in parahippocampal regions and this relationship was more strongly observed for neutral stimuli compared to emotional stimuli.